2019
DOI: 10.1161/circulationaha.119.041766
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Bleeding With Ticagrelor Versus Clopidogrel in Korean Patients With Acute Coronary Syndromes Intended for Invasive Management

Abstract: Background: Owing to the differential propensity for bleeding and ischemic events with response to antiplatelet therapy, the safety and effectiveness of potent P2Y12 inhibitor ticagrelor in East Asian populations remain uncertain. Methods: In this multicenter trial, 800 Korean patients hospitalized for acute coronary syndromes with or without ST elevation and intended for invasive management were randomly assigned to receive, in a 1:1 ratio, ticagrelor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 30 publications
7
128
2
1
Order By: Relevance
“…Our results are consistent with those from the PHILO study conducted in East-Asian patients, which reported that the incidence of bleeding and cardiovascular events was higher in ticagrelor users than in clopidogrel users [16]. In comparison with clopidogrel, a recent randomized controlled trial in Korean patients with ACS also reported a higher risk of bleeding with ticagrelor but found no significant difference in cardiovascular death [24]. These observations are in line with the phenomenon referred to as the ''East Asian paradox,'' which describes the vulnerability to bleeding and resistance to ischemic events of East Asian populations compared with Caucasians [25].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with those from the PHILO study conducted in East-Asian patients, which reported that the incidence of bleeding and cardiovascular events was higher in ticagrelor users than in clopidogrel users [16]. In comparison with clopidogrel, a recent randomized controlled trial in Korean patients with ACS also reported a higher risk of bleeding with ticagrelor but found no significant difference in cardiovascular death [24]. These observations are in line with the phenomenon referred to as the ''East Asian paradox,'' which describes the vulnerability to bleeding and resistance to ischemic events of East Asian populations compared with Caucasians [25].…”
Section: Discussionsupporting
confidence: 91%
“…However, East Asian patients with ACS undergoing PCI may be more likely to have bleeding events than Western patients with potent P2Y12 receptor inhibitors. [22][23][24] For this reason, more medical attention is required to maintain an extended duration of potent P2Y12 receptor inhibitor for East Asian patients with ACS who undergo PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, pharmacological agents showing EPC-mobilizing effect (e.g., cilostazol or ticagrelor) may provide a therapeutic option to promote vascular repair and prevent thrombotic events after stent implantation. However, ticagrelor versus clopidogrel treatment significantly increased bleeding risk without a protective benefit against thrombotic events in Asian patients [18,19]. Considering the net clinical benefit without a trade-off of bleeding risk, triple antiplatelet therapy with cilostazol, clopidogrel, and aspirin may be a plausible regimen in ACS patients at high-bleeding risk (e.g., East Asians, elderly, and diabetes).…”
Section: Discussionmentioning
confidence: 99%
“…EPC-mobilizing effect of ticagrelor might be mediated by enhancement of plasma adenosine concentration beyond its antiplatelet effect [15,17]. Although the guidelines recommended ticagrelor or prasugrel in ACS patients, clinical data from East Asians have shown significantly increased risk of serious bleeding without definite benefit in ischemic risk among ACS patients [18,19].…”
Section: Introductionmentioning
confidence: 99%